Ciprofloxacin Concentrations 1/1000th the MIC Can Select for Antimicrobial Resistance in N. gonorrhoeae-Important Implications for Maximum Residue Limits in Food - Natalia González; Saïd Abdellati; Irith De Baetselier; Jolein Gyonne Elise Laumen; Christophe Van Dijck; Tessa de Block; Sheeba Santhini Manoharan-Basil; Chris Kenyon (MDPI AG, 2022)
Background: Concentrations of fluoroquinolones up to 200-fold lower than the minimal inhibitory concentration (MIC) have been shown to be able to select for antimicrobial resistance in E. coli and Salmonella spp. (the minimum selection concentration-MSC). We hypothesized that the low concentrations of quinolones found in meat may play a role in the genesis of quinolone resistance in Neisseria gonorrhoeae. We aimed to (i) establish the ciprofloxacin MSC for N. gonorrhoeae and (ii) assess if, at the ecological level, the prevalence of gonococcal ciprofloxacin resistance is associated with the concentration of quinolones used in food animal production, which is an important determinant of long-term low-dose exposure to ciprofloxacin in humans. Methods: (i) To assess if subinhibitory ciprofloxacin concentrations could select for de novo generated resistant mutants, a susceptible WHO-P N. gonorrhoeae isolate was serially passaged at 1, 1:10, 1:100 and 1:1000 of the ciprofloxacin MIC of WHO-P (0.004 mg/L) on GC agar plates. (ii) Spearman's correlation was used to assess the association between the prevalence of ciprofloxacin resistance in N. gonorrhoeae and quinolone use for animals and quinolone consumption by humans. Results: Ciprofloxacin concentrations as low as 0.004 µg/L (1/1000 of the MIC of WHO-P) were able to select for ciprofloxacin resistance. The prevalence of ciprofloxacin resistance in N. gonorrhoeae was positively associated with quinolone use for food animals (ρ = 0.47; p = 0.004; N = 34). Conclusion: Further individual level research is required to assess if low doses of ciprofloxacin from ingested foodstuffs are able to select for ciprofloxacin resistance in bacteria colonizing humans and other species.